WHAT DO WE KNOW ABOUT WOMEN DEACONS? - Zagano, Phyllis; Pottier, Bernard (Asian Horizons, 2019)
Pope Francis’s decision to establish a Commission for the Study of the Diaconate of Women in August 2016 reemphasizes the question: what do we know about women deacons? We know they existed. There is ample literary, epigraphical, and historical evidence that women deacons ministered in the West at least to the 12th century, and longer in the East. That they existed presents three questions: What do we know about the liturgical ceremonies bishops used to create women deacons? What do we know about their tasks and duties? What do we know about the theology of the diaconate that would admit or restrict women from diaconal ordination?